Determination of furosemide in pharmaceutical formulations by diffuse reflectance spectroscopy - Gotardo, M. A.; Gigante, A. C.; Pezza, Leonardo [UNESP]; Pezza, Helena Redigolo [UNESP] (Elsevier B.V., 2004)
In this report an analytical method to determine furosemide by using diffuse reflectance spectroscopy is presented. This study shows that this technique can give quantitative results using spot test analysis, particularly in the case of pharmaceuticals containing furosemide. The color spot test could be obtained by reaction between furosemide with p-dimethylaminocinnamaldehyde, in acid medium. This reaction produced a stable complex on filter paper after heating to 80degreesC for 5 min. All reflectance measurements were carried out at 585 nm and the linear range was from 7.56 x 10(-3) to 6.05 x 10(-2) mol l(-1), with a correlation coefficient of 0.999. The limit of detection was estimated to be 2.49 x 10(-3) mol l(-1) (R.S.D. = 1.7%) and the effect of common excipients on the reflectance measurements was evaluated. The method was applied to determine furosemide in commercial brands of pharmaceuticals. The results obtained by the proposed method were favorably compared with those of the official method, showing for the first time ever that quantitative spot test analysis by diffuse reflectance could be successfully used to determine furosemide in tablets. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: diffuse reflectance spectroscopy; furosemide; spot test; p-dimethylaininocinainaldehyde